Nível de maturidade e BSC para avaliação de desempenho do serviço logístico - Silva, Pedro Artur Aguiar Gama (2016)
With the increasing competitiveness among organizations in the search for the customer retention, efficient logistics services have become a priority factor to get better results. In order to achieve these results, a better performance is necessary, having as strategy the assessment of the logistics service performance, in order to understand the efficiencies and deficiencies that the process brings. Before the aforementioned scenario, the objective of this research is to propose a method tha includes level of maturity and balanced scorecard to evaluate the performance of the logistics service. In order to reach this objective, the research was started with a bibliographical research based on the ProcKnow-C methodology, whose focus is the survey the methods of evaluation performance of logistics service present in the literature and in the systemic analysis of the same, having as product a classification matrix, relating the methods with evaluation criteria. The proposed method was applied to a machines and equipments rental company located in Espírito Santo. As a result, the method was able to evaluate the performance of the company's logistics service, where it was discovered at what level of performance the company is.